The Future of Learning Institutions in a Digital Age - Davidson, Cathy N. (The John D. and Catherine T. MacArthur Foundation Reports on Digital Media and Learning, 2009)
This John D. and Catherine T. MacArthur Foundation Report is a redaction of the argument in our book-in-progress, currently titled The Future of Thinking: Learning Institutions in a Digital Age. That book, to be published in 2010, is merely the concrete (paper and online) manifestation and culmination of a long, complex process that brought together dozens of collaborators, face to face and virtually. The focus of all of this intense interchange was the shape and future of learning institutions. Our charge was to accept the challenge of an Information Age and acknowledge, at the conceptual as well as at the methodological level, the responsibilities of learning at an epistemic moment when learning itself is the most dramatic medium of that change. Technology, we insist, is not what constitutes the revolutionary nature of this exciting moment. It is, rather, the potential for shared and interactive learning that Tim Berners-Lee and other pioneers of the Internet built into its structure, its organization, its model of governance and sustainability.